Proceso de Búsqueda de Identidad Sexual en Adolescentes desde sus vivencias (2023)
This work aimed to understand how the process of sexual identity occurs in three adolescents from caicedonia Valle del cauca; the supporting authors of the research were Ardila (2007) and cass (1984); of a phenomenological, qualitative, descriptive nature, with the participation of theree adolescents; the category was homosexual identity, with its respective subcategories such as confusión, camparison, tolerance, pride and identity synthesis.T